(untitled) (Scientific journal of the Fergana State University, 2026)
This article explores innovative art-pedagogical technologies as a means of developing the aesthetic and creative competence of future teachers in the context of digital education. It outlines the methodological foundations of art pedagogy and defines the principles of integrating digital technologies with artistic and creative activities. The paper presents examples of effective digital art practices that foster creative thinking, emotional responsiveness, and aesthetic perception.